Students' critical thinking skills profile: constructing best strategy in teaching chemistry - Budi Utami; Sulistyo Saputro; Ashadi Ashadi; Mohammad Masykuri; Riezky Maya Probosari; Alimin Sutanto (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2018)
The purpose of this study was to determine the profile of critical thinking skills of senior high school students. The paper-based essay questions and the questionnaires were used as the instruments to measure critical thinking skills in daily chemistry problems, which is based on Facione’s critical thinking aspects included interpretation, analysis, evaluation, inference, explanation, and self-regulation. The research was conducted in one of government senior high school in Central Java, Indonesia. The descriptive-qualitative method was used for the research method. The qualitative approach was used to analyze the data by using essay questions and questionnaires. The criteria for critical thinking skills were categorized as null, low, medium, and high. The result showed that most of the students have weak or low skill in critical thinking, especially in analysis, evaluation, explanation, and self-regulation whether their skill of interpretation and inference are medium. This finding can be used to develop a new strategy in teaching chemistry related to critical thinking skill.